2009
DOI: 10.1143/jpsj.78.073705
|View full text |Cite
|
Sign up to set email alerts
|

Possible Sign-Reversings-Wave Superconductivity in Co-Doped BaFe2As2Proved by Thermal Transport Measurements

Abstract: Thermal transport measurements have been performed on single-crystalline Co-doped BaFe 2 As 2 down to 0.1 K and under magnetic fields up to 7 T. Significant peak anomalies are observed in both thermal conductivity and thermal Hall conductivity below T c as an indication of the enhancement of the quasiparticle mean-free path. Moreover, we find a sizable residual T -linear term in thermal conductivity, possibly due to a finite quasiparticle density of states in the superconducting gap induced by impurity pair br… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
32
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 26 publications
(30 reference statements)
3
32
0
Order By: Relevance
“…In a recent study, a large κ 0 /T was reported [16] in a Co-Ba122 sample with T c and residual resistivity ratio similar to our x = 0.074 sample, amounting to 60 % of κ N /T , compared with less than 1-2 % in our sample. This stands in contradiction not only with our results on more than 10 crystals of Co-Ba122 at various dopings, but also with previous results on K-Ba122 [3] and Ni-doped BaFe 2 As 2 (Ni-Ba122) [17], where in all cases κ 0 /T ≃ 0 at H = 0.…”
supporting
confidence: 70%
“…In a recent study, a large κ 0 /T was reported [16] in a Co-Ba122 sample with T c and residual resistivity ratio similar to our x = 0.074 sample, amounting to 60 % of κ N /T , compared with less than 1-2 % in our sample. This stands in contradiction not only with our results on more than 10 crystals of Co-Ba122 at various dopings, but also with previous results on K-Ba122 [3] and Ni-doped BaFe 2 As 2 (Ni-Ba122) [17], where in all cases κ 0 /T ≃ 0 at H = 0.…”
supporting
confidence: 70%
“…By contrast, a large κ 0 /T was observed in BaFe 1.86 Co 0.14 As 2 . 30 For the prototype FeSe x (T c = 8.8 K) superconductor, the thermal conductivity shows clear behavior of multiple nodeless superconducting gaps. 31 In two superconductors with lower T c , κ 0 /T of BaNi 2 As 2 (T c = 0.7 K) is consistent with a dirty fully gapped superconductivity, 32 while LaFePO (T c = 7.4 K) appears to have a finite κ 0 /T , suggesting the gap on some band may have nodes.…”
Section: Introductionmentioning
confidence: 98%
“…30 It has been noted that the large κ 0 /T in zero field observed in BaFe 1.86 Co 0.14 As 2 by Machida et al 30 may be extrinsic.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Some early measurements, including angle -resolved electron spectroscopy [1][2][3][4], point contact spectroscopy [5], penetration depth [6,7] and specific heat [8] were interpreted in a framework of fully gapped superconductivity. Others, such as NMR [9], penetration depth [10][11][12][13] and thermal conductivity [14,15] have suggested a strongly anisotropic gap. More recent systematic measurements of thermal conductivity over the whole doping phase diagram in Ba(Fe 1−x Co x ) 2 As 2 (FeCo-122) single crystals have shown a clear evolution towards a more anisotropic gap in the overdoped regime [16].…”
mentioning
confidence: 99%